Urinary tract infection after voiding cystourethrogram. Issue 4 (August 2017) - Johnson, E.K.; Malhotra, N.R.; Shannon, R.; Jacobson, D.L.; Green, J.; Rigsby, C.K.; Holl, J.L.; Cheng, E.Y.
Summary: Background: Reported rates of post-procedural urinary tract infection (ppUTI) after voiding cystourethrogram (VCUG) are highly variable (0–42%). Objective: This study aimed to determine the risk of ppUTI after cystogram, and evaluate predictors of ppUTI. Study design: A retrospective cohort study of children undergoing VCUG or radionuclide cystogram (henceforth 'cystogram') was conducted. Children with neurogenic bladder who underwent cystogram in the operating room and without follow-up at the study institution were excluded. Incidence of symptomatic ppUTI within 7 days after cystogram was recorded. Predictors of ppUTI were evaluated using univariate statistics. Results: A total of 1108 children (54% female, median age 1.1 years) underwent 1203 cystograms: 51% were on periprocedural antibiotics, 75% had a pre-existing urologic diagnosis (i.e., vesicoureteral reflux (VUR) or hydronephrosis; not UTI alone), and 18% had a clinical UTI within 30 days before cystogram. Of the cystograms, 41% had an abnormal cystogram and findings included VUR (82%), ureterocele (6%), and diverticula (6%). Twelve children had a ppUTI (1.0%; four girls, five uncircumcised boys, three circumcised boys; median age 0.9 years). Factors significantly associated with diagnosis of a ppUTI (Summary fig. ) included: pre-existing urologic diagnosis prior to cystogram (12/12, 100% of patients with ppUTI), abnormal cystogram results (11/12, 92%), and use of periprocedural antibiotics (11/12, 92%). All 11 children with an abnormal cystogram had VUR ≥ Grade III. However, among all children with VUR ≥ Grade III, 4% (11/254) had a ppUTI. Discussion: This is the largest study to date that has examined incidence and risk factors for ppUTI after cystogram. The retrospective nature of the study limited capture of some clinical details. This study demonstrated that the risk of ppUTI after a cystogram is very low (1.0% in this cohort). Having a pre-existing urologic diagnosis such as VUR or hydronephrosis was associated with ppUTI; therefore, children with moderate or high-grade VUR on cystogram may be at highest risk. Development of ppUTI after cystogram also highlighted the potential for a delay in diagnosis or oversight of a healthcare-associated infection due to several factors: 1) cystograms may be ordered, performed/interpreted, and followed up by multiple different providers; and 2) such infections are not captured by traditional healthcare-associated infection surveillance strategies. Conclusions: The risk of ppUTI after a cystogram is very low. Only children with pre-existing urologic diagnoses developed ppUTI in this study. This study's findings suggest that children undergoing a cystogram should not be given peri-procedural antibiotic prophylaxis for the sole purpose of ppUTI prevention. Summary Fig Comparison of children developing post-procedural UTI (ppUTI) vs no ppUTI: significant associations.